Differential host defense against multiple parasites in ants - Hashim, Rosli; Witte, V.; von Beeren, C.; Maruyama, M. (2011)
Host-parasite interactions are ideal systems for the study of coevolutionary processes. Although infections with multiple parasite species are presumably common in nature, most studies focus on the interactions of a single host and a single parasite. To the best of our knowledge, we present here the first study on the dependency of parasite virulence and host resistance in a multiple parasite system. We evaluated whether the strength of host defense depends on the potential fitness cost of parasites in a system of two Southeast Asian army ant hosts and five parasitic staphylinid beetle species. The potential fitness costs of the parasites were evaluated by their predation behavior on host larvae in isolation experiments. The host defense was assessed by the ants' aggressiveness towards parasitic beetle species in behavioral studies. We found clear differences among the beetle species in both host-parasite interactions. Particular beetle species attacked and killed the host larvae, while others did not. Importantly, the ants' aggressiveness was significantly elevated against predatory beetle species, while non-predatory beetle species received almost no aggression. As a consequence of this defensive behavior, less costly parasites are more likely to achieve high levels of integration in the ant society. We conclude that the selection pressure on the host to evolve counter-defenses is higher for costly parasites and, thus, a hierarchical host defense strategy has evolved that depends on the parasites' impact.